PENGARUH KINERJA KEUANGAN TERHADAP CAPITAL GAIN PADA INDUSTRI PROPERTI DI BURSA EFEK INDONESIA ( PERIODE TAHUN 2008 – 2013 ) - Ida Wahyuni; Said Djamaluddin (Jurnal Ilmiah Manajemen dan Bisnis, 2016)
This study aims to examine and analyze the eﬀect of Financial Performance ( Current Ratio, Debt to Equity Ratio,Total Assets Turn Over and Return on Equity) against Capital Gains on Industrial Property in IndonesiaStock Exchange Data Research is a monthly data for the period of observation for 6 years ( Januari 2008 toDecember 31, 2013). Sampling method used purposive sampling of the population of 40 propertycompanies, 29 companies met the criteria as a sample. The method of analysis usedin this study is thetechnique correlation and regression technique. The results showed Current Ratio, Debt to Equity Ratio,Return on Equity and Total assets Turn Over simultaneously is weak and not signiﬁcant to Capital Gains isindicated by coeﬃcient of determination ( R2) is 0,044 or 4,4 % while the remaining 95,6 % inﬂuenced byother factors. In Partial Liquidity (Current Ratio), Solvency (Debt of Equity Ratio), Activities (Total AssetsTurn Over) eﬀect is weak and insigniﬁcant , and Proﬁtability (Return on Equity) eﬀect is weak andsigniﬁcant agains Capital Gains .